Perkembangan Kognitif dan Motorik Anak Usia Dini melalui Pendekatan Pembelajaran (Sekolah Tinggi Agama Buddha Nalanda, 2023)
Cognitive and motor development in early childhood through a holistic learning approach. We identified the positive impact of implementing experience-based and interactive learning methods on cognitive abilities, such as problem solving and children's creativity. Apart from that, this approach also shows improvements in children's motor development, such as eye-hand coordination and gross motor skills. The implications of these findings highlight the importance of using comprehensive learning strategies in supporting the overall growth of early childhood. Motor development is one aspect that must be considered in early childhood. Motor development is often used as a benchmark to prove that children are growing and developing well. Motor development is one aspect that must be considered in early childhood development. Motor development is often used as a benchmark to prove that children grow and develop well. Motor development is something that discusses coordinated physical movements so that in its development required a variety of appropriate stimulation for early childhood. This stimulation can be provided by parents, teachers, and the environment both at home and in the school environment by providing a supportive learning environment for early childhood motor development. Giving stimulation is an effort made by adults in providing facilities and optimal opportunities for optimal development. Providing a lot of time for children to do activities that support their motor development and proper supervision is one of the right efforts in supporting the development of motor physical early childhood.